2020
DOI: 10.1002/adem.202000187
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Characteristics and Mechanical Properties of Repaired Titanium Alloy Blade by Arc Additive Manufacturing Process

Abstract: To improve repair efficiency and achieve a high‐quality repair layer, wire and arc additive manufacturing process is used in this study to repair missing‐angle Ti‐6Al‐4V blade. The deposition layer with a mixed equiaxed β and columnar grain can be obtained by optimizing the deposition speed and single layer height. According to the characteristics of β grain, the typically repaired thin‐walled part is divided into four representative areas, including heat affected zone (HAZ), bottom layer, middle layer, and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8] Among various Ti alloys, Ti-6Al-4V alloy, which belongs to α þ β dual-phase Ti alloys, possesses good fatigue resistance, strength, and corrosion resistance. [9][10][11][12][13] Therefore, Ti-6Al-4V alloys are applied in biological fields, especially for hard tissue replacements (such as orthopedic implants). [14][15][16] However, the disadvantages of Ti-6Al-4V alloys, including low hardness, strong biological inertness, and poor wear resistance, are also apparent, which restrict their further applications.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Among various Ti alloys, Ti-6Al-4V alloy, which belongs to α þ β dual-phase Ti alloys, possesses good fatigue resistance, strength, and corrosion resistance. [9][10][11][12][13] Therefore, Ti-6Al-4V alloys are applied in biological fields, especially for hard tissue replacements (such as orthopedic implants). [14][15][16] However, the disadvantages of Ti-6Al-4V alloys, including low hardness, strong biological inertness, and poor wear resistance, are also apparent, which restrict their further applications.…”
Section: Introductionmentioning
confidence: 99%
“…The x‐ray diffraction results confirmed the presence of strengthening compounds (Cr 7 C 3 and Cr 3 C 2 carbides) and intermetallic precipitates with W (Co 4 W 2 C) and these phases improved the hardness and wear performance of stellite 6 in the hard overlays [24]. Wire arc additive manufacturing was used to repair missing‐angle Ti‐6Al‐4V blades and attained comparable tensile properties than cast and wrought counterparts [25]. The influence of process variables was investigated systematically for depositing stainless steel 304L single‐pass beads to repair worn‐out parts [26].…”
Section: Introductionmentioning
confidence: 74%
“…They extracted tensile test samples from different regions of the blade-like geometry and showed that they have comparable mechanical tensile properties according to the material specification in an as-welded condition [14]. Liu et al used WA-DED to repair a Ti6Al4V blade and obtained mechanical tensile properties for the as-welded condition, which are in the range of other manufacturing processes [15]. Yan et al demonstrated the Laser Metal Deposition (LMD) process for a Ti6Al4V blade, where lower mechanical tensile properties than for WA-DED and the casting condition TC4 were achieved [16].…”
Section: Investigation Of the Obtained Mechanical Properties By Destr...mentioning
confidence: 99%